Optimization of power‐efficient wireless mesh networks in outdoor and indoor environments in Japan. Issue 6 (12th September 2015) - Kamimura, Kohei; Hayashi, Hitoshi
<x xml:space="preserve">Abstract</x> This paper proposes the optimization of power‐efficient wireless mesh networks in outdoor and indoor environments, particularly for gas metering in Japan. We investigate the effect on total power consumption by changing the output power and allocated frequency band of a gas metering system. From the simulation results, we show that these changes are effective in achieving low power consumption. © 2015 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.